2021
DOI: 10.1097/hco.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Global interventions in hypertension: new and emerging concepts

Abstract: Purpose of reviewHypertension (HTN) is the most prevalent risk factor for cardiovascular disease (CVD) worldwide, affecting 1.39 billion people. This review discusses recent literature regarding the global burden of HTN and emerging concepts in prevalence, treatment, and control in different regions around the globe. Recent findingsCommunity-based interventions and telemedicine may be useful in increasing access to care and identifying/assisting patients with HTN, especially in populations with geographical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Obesity and hypertension, two major risk factors for CVD, contribute to global health and economic burdens (1,2,5,6,41). Given the dramatic increase in hypertension with the significant rise in obesity, early detection of hypertension using ORI screening could effectively prevent future hypertension and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and hypertension, two major risk factors for CVD, contribute to global health and economic burdens (1,2,5,6,41). Given the dramatic increase in hypertension with the significant rise in obesity, early detection of hypertension using ORI screening could effectively prevent future hypertension and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a risk factor for cardiovascular diseases (CVD) and death; thus, it is an essential global health threat (1,2). A nationwide epidemiological study involving 451,755 residents from 31 provinces in China showed that the prevalence of hypertension among adults in China was 23.2% (3).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a critical risk factor for cardiovascular disease [ 1 ]. The prevalence of hypertension has been increasing worldwide year by year.…”
Section: Introductionmentioning
confidence: 99%
“…Ten million people in the world will have died of cancer in 2020 [ 4 ]. Hypertension is the main risk factor for cardio-cerebrovascular disease [ 5 ]. Globally, more than a quarter of the population is hypertensive [ 6 ].…”
Section: Introductionmentioning
confidence: 99%